Study of histological and biochemical changes induced by the mycotoxin xyralenone in albino mice (Journal of the College of Basic Education, 2022)
This study aimed to demonstrate the histological and biochemical effects in the liver and kidney tissues of male albino mice under the influence of zealenone toxin extracted from the isolate of the zealenone-producing fungus Fusarium graminearum, at a concentration of (2) mg/kg in a single dose and repeated doses of the toxin and administered orally. The rats were divided into three groups ( 5 rats per group) taking into account the live body weight and the weights of the liver and kidneys, a group was treated with a single dose of poison and left for two days (T1), and another group was treated with two doses per week for a week (T2) and a group was treated with two doses every week for two weeks (T3), and it has A control group was taken for each treatment and treated with the solution in which the mycotoxin was dissolved (1% dimethyl sulfur).